TRAINING AND ASSISTANCE IN QUANTITATIVE DATA PROCESSING USING IBM SPSS STATISTICS FOR TARBIYAH STUDENTS - Athiurobbi, Khasna; Isnaini Choirunisak (International Journal of Multidisciplinary Reseach, 2026)
Last semester students of the Faculty of Tarbiyah often face obstacles in quantitative data analysis. This community service program aims to improve the statistical data processing skills of fifth semester students using IBM SPSS software version 25. The intervention was carried out through a structured training program consisting of eight offline meetings, applying methods such as tutorials, workshops, and simulations. Students were involved in hands-on practice covering descriptive statistics, instrument test, assumptions of statistical tests, and hypothesis test (one-sample t-test, paired, and independent). The effectiveness of the program was evaluated using independent assignments, whose scores were analyzed with a one-sample t-test against a test value of 70. The results showed significant progress, with an average participant score of 78.08, which was statistically higher than the minimum standard. The Sig (2-tailed) value was 0.000, which means that this training was effective in training data processing competencies using IBM SPSS. The activity was closed with a follow-up in the form of creating a consultation group and disseminating material to ensure continuous assistance. This training effectively improved students' data analysis competencies, contributing to an increase in student research capacity and academic quality in the university environment.